In vitro colonic fermentation of Mexican “taco” from corn-tortilla and black beans in a Simulator of Human Microbial Ecosystem (SHIME®) system - Cárdenas-Castro, Alicia Paulina; Bianchi, Fernanda [UNESP]; Tallarico-Adorno, María Angela; Montalvo-González, Efigenia; Sáyago-Ayerdi, Sonia G.; Sivieri, Katia [UNESP] (Elsevier, 2018)
A Mexican staple food prepared with corn “tortilla” (Zea mays L.) and common beans (Phaseolus vulgaris L.) is named as “taco”. It was fermented in an in vitro colonic Simulator of Human Microbial Ecosystem (SHIME®) to evaluate the effect in short chain fatty acids (SCFA), ammonia production, and the growth of total presumptive counts for anaerobic bacteria, Lactobacillus spp., Bifidobacterium spp., Clostridium spp., and total coliforms in the three simulated reactors of the human colon. After two weeks of stabilization, the simulator was fed during 9 days with the mixture of 50 g of beans and 50 g of tortilla mixed with 100 mL of carbohydrate based medium. Every third day, samples were collected from the three simulated colon vessels for the corresponding analysis. The production of the SCFA was higher during the treatment period than the basal period in the three colon sections. The acetate was produced in higher concentration (191.9 mmol/L) than propionate and butyrate (29.1 and 55.0 mmol). During the treatment period, the higher molar ratio (%) for acetate, propionate, and butyrate were 84: 14: 24, respectively. The ammonia ions as well as the growth of presumptive coliforms were reduced (p < 0.05) in the three simulated colon vessels during the treatment. Finally, in vitro fermentation of Mexican “taco” showed a possible potential functional profile of an ancestral staple food due to the production of SCFA that may exert beneficial effects.
Keywords: Ammonium; Beans; Fermentation; Microbiota; SHIME; Short chain fatty acids; Taco; Tortilla